2011
DOI: 10.1242/dev.067686
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal development of adipose tissue

Abstract: SUMMARYAdipose tissue is a structure highly specialized in energy storage. The adipocyte is the parenchymal component of adipose tissue and is known to be mesoderm or neuroectoderm in origin; however, adipocyte development remains poorly understood. Here, we investigated the development of adipose tissue by analyzing postnatal epididymal adipose tissue (EAT) in mouse. EAT was found to be generated from non-adipose structure during the first 14 postnatal days. From postnatal day 1 (P1) to P4, EAT is composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(197 citation statements)
references
References 57 publications
10
171
0
2
Order By: Relevance
“…Moreover, treating adipose tissue fragments with TZDs increased angiogenic sprout formation and similar results were obtained in vivo in mouse (Gealekman et al, 2008). Inhibiting or activating angiogenic factors controls adiposity; in the epididymal fat depot, blunting VEGF/VEGFR2 signaling inhibits fat pad formation (Han et al, 2011), and transgenically overexpressing VEGF in mature adipocytes enhances vasculogenesis and reduces adipocyte size (Nishimura et al, 2007;Sun et al, 2012), demonstrating the orchestration between blood vessels and adipocytes.…”
Section: The Adipose Stem Cell Niche: Blood Brotherssupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, treating adipose tissue fragments with TZDs increased angiogenic sprout formation and similar results were obtained in vivo in mouse (Gealekman et al, 2008). Inhibiting or activating angiogenic factors controls adiposity; in the epididymal fat depot, blunting VEGF/VEGFR2 signaling inhibits fat pad formation (Han et al, 2011), and transgenically overexpressing VEGF in mature adipocytes enhances vasculogenesis and reduces adipocyte size (Nishimura et al, 2007;Sun et al, 2012), demonstrating the orchestration between blood vessels and adipocytes.…”
Section: The Adipose Stem Cell Niche: Blood Brotherssupporting
confidence: 65%
“…Their microscopic studies also indicated that angiogenesis recruits adipose stem cells and stimulates these stem cells to differentiate (Crandall et al, 1997). These observations were supported by studies of Han et al, whose data suggested that angiogenesis precedes visceral epididymal adipose tissue depot development (Han et al, 2011). This relationship between vessels and adipose lineage cells appears to be reciprocal, as adipocyte stem cells stimulate blood vessel formation.…”
Section: The Adipose Stem Cell Niche: Blood Brothersmentioning
confidence: 68%
“…We favour the hypothesis that the range of factors or culture conditions required to induce adipocyte differentiation of MSCs derived from adult tissues and from embryonic-like cells could differ. The low hiPSC-MSC adipogenic capacity is a reminiscence of an earlier observation reported by Han et al [37] . The authors observed that epididymal adipose tissue, which undergoes postnatal development in mouse, is composed of multipotent progenitor cells that meet the MSC criteria but lack an adipogenic capacity in vitro.…”
Section: Derived Mscssupporting
confidence: 73%
“…The metabolic state and gene expression in these cells directed or regulated by moderate nutrients and conditions are coordinated toward this fate for cells, and imprint onto the subsequent organogenesis. During organogenesis, the cells of embryonic mesoderm give rise to bones, muscles [19], and adipose tissues [20] in vertebrates, and to muscles in Drosophila [21]. Therefore, the regulation of both cell state and gene classes in mesoderm with proposed nutrient gradient during gastrulation fits with the generated phenotypes, in further supporting the rationality of the theory.…”
Section: Phenotypic Fates Of Three Germ Layers In Gastrulasupporting
confidence: 57%
“…The ectoderm is destined to differentiate into the neural progenitors and epidermal progenitors in vertebrates [16], and to neural cells [17] and epidermal cuticle in Drosophila [18]. The mesoderm is destined to differentiate into the bones, muscles [19], and adipose tissues [20] in vertebrates, and to muscles in Drosophila [21].…”
Section: Nutrient Preserving the Trilaminar Fates In Gastrula Versus mentioning
confidence: 99%